Detection of Escherichia coli Contamination Using Most Probable Number (MPN) Methods of Jamu Pahitan in Singaparna District, Tasikmalaya - Syifa Sri Rahmawati; Richa Mardianingrum; Susanti Susanti (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Indonesians consume a lot of traditional jamu, including jamu pahitan. However, the hygiene aspect in the production and serving process is often neglected, so it has the potential to be contaminated with Escherichia coli. Using the MPN method, this study analyzed the presence of E. coli in jamu pahitan sold in Singaparna District. A total of 10 samples were tested, taken from jamu vendors who used plastic bottle packaging. The MPN test results showed that all samples contained E. coli with MPN values ranging from 6.0-1100 g/mL. None of the samples met food safety standards based on SNI 7388:2009, because the maximum limit of E. coli in drinks is <3 MPN/mL. The results of Gram staining of bacteria showed that the bacteria found were bacilli, red in color, including Gram-negative bacteria, indicating the presence of E. coli bacteria.